The Impact of Work Motivation and Work Discipline on Employee Performance in Enhancing Business Performance at PT. Hamatetsu Indonesia - Utari, Reka Tri; Jamaludin, Asep; Nandang, Nandang (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aims to investigate and analyze the influence of Work Motivation and Work Discipline on Employee Performance at PT. Hamatetsu Indonesia. This research is quantitative in nature and employs a causal method with a survey approach to the employees of PT Hamatetsu Indonesia. The population set for this study is 172 employees, with a sample size of 120 determined using the Slovin formula and employing simple random sampling technique directed at PT. Hamatetsu Indonesia employees. The data used in this study are primary data obtained through the distribution of questionnaires. The analytical tools used in this research include multiple regression, correlation, coefficient of determination, and hypothesis testing. The results of the study indicate that simultaneously, work motivation and work discipline have a significant influence on employee performance. Specifically, work motivation has a significant influence on employee performance. Additionally, work discipline also has a significant influence on employee performance. It is evident that work motivation and work discipline positively influence the enhancement of employee performance. The limitations of this study only focus on two influencing variables and need further development in terms of research variables and research objects. This study can be considered by institutions to contemplate factors that can improve employee performance. It is hoped that future research will add more variables and focus on different business fields.